Biology of the tomato leafminer Liriomyza sativae (Diptero: Agromyzidae) - SALAS, JORGE; PARRA, ALEXIS (Revista Colombiana de Entomología, 1994)
Biological aspects of the tomato leafminer Liriomyza sativae Blanchard (Diptera: Agromyzidae) were studied under laboratory conditions (T=26°C; R.H=67%) during the first semester of 1992. The mean duration of the different developmental stages was: egg 3.5 days; larva 7.0 days; prepupa 4.5 hours and pupa 8.0 days. The mean duration of the life cycle from egg to adult was 18.5 days. Adults males and females fed with 5% honey-water solution lasted 6.1 and 10.0 days, respectively. Preoviposition and oviposition periods were 1.0 and 7.5 days. Fecundity was 24.4 eggs/female, whereas fertility was 59%. Three larval in-stars were registered using Dyar's law and based on the size of the mouth hooks. Sex ratio was 1 male: 1.77 female.